Charge microheterogeneity of the major capsid protein of polyoma virus. - Hare, J D (1982)
The behavior in isoelectric focusing of the major capsid polypeptide VPI of several strains of polyoma virus was studied. Two previously recognized phenomena were reexamined, namely, (i) the separation of the VP1 polypeptide into multiple subspecies differing only slightly from each other in apparent isoelectric point and (ii) strain differences in the overall apparent net charge of the family of VP1 subspecies. It was found that the pattern of subspecies was reproducible when focusing was initiated from either the basic or acidic region of the gel, keeping the ampholyte mixture constant. However, individual subspecies were unstable, and labeled polypeptide could be shifted dramatically by either refocusing of separated subspecies or by altering the concentration of ampholytes. These findings suggest that protein-protein and protein-ampholyte interactions play an important role in the generation of this charge heterogeneity. The basis for the overall charge difference between the VP1 of 3049 virus and several other strains (lpD, lpS, ts59, and A2) was studied, using recombinant viruses constructed of specific sequences derived from 3049 and lpD genomes. The portion of the VP1 polypeptide carrying the altered charge could be mapped to the body of the molecule 3' to the HindIII site at 45.0 map units (3,918 base pairs). This clearly segregates the VP1 charge phenotype from the cyc phenotype of 3049 in which capsid proteins are overproduced and accumulate in the cytoplasm of infected cells.